A Robust Multi-Source Automatic Power Supply System Utilizing Mains, Generator, Wind, and Solar Energy - Divya, Dasari; K, Sree Latha; Alchilibi, Haider; Farhan, Tahir Toma; Marouf, Maha; Singh, Sourav; Bhargavi, Peruka; Prasad, Gyara Bhanu (2024 International Conference on Augmented Reality, Intelligent Systems, and Industrial Automation (ARIIA), 2024)
The main scope of this research is to ensure the consumption of the power supply from mains, generator, Wind and solar sources, optimally by using an appropriate programmed microcontroller in the most effective way. Emergency power systems are the types of systems that may include lighting, generators, fuel cells and other apparatus, to provide backup power resources in crisis or when the regular systems fail. In this setup, we use four switches to create the corresponding breakdown of that power supply source. When any of the switches is turned off, it shows the absence of that particular source. Switches are used to control the signal flow through microcontroller. The commands of the microcontroller are fed to the relay driver IC, which switches appropriate relay to maintain uninterrupted supply to the load. It is indicated by using a lamp which fed through a single power supply from the mains initially. On the failure of this mains supply which has been activated by pressing the appropriate switch, the load gets supply from the next available source for instance. If the Wind also fails, it switches over to the next available source, and likewise.